Exploration of Glow-in-the-Dark Pigment and Resin Materials in Relation to Types and Illumination Duration in Craft Products - Chici Yuliana Nadi; Sri Marwati; Pratita Rara Raina (Corak, 2026)
This research was motivated by the limited availability of structured experimental data on innovative materials in the fields of craft and art. Glow-in-the-dark pigments and resin were chosen as the main focus due to their potential in experimental and contemporary creation. The purpose of this study is to explore the characteristics of glow-in-the-dark pigments and resin, and to examine the effects of light type and exposure duration on the visual quality of craft products produced. The approach used is practice-led research, positioning the creation process as the primary source of knowledge. The results show that epoxy resin has advantages over polyester and UV resin, while strontium aluminate–based pigments produce higher light intensity and longer afterglow duration than zinc sulfide. The experiments indicate that CAST R-GID and TOP R-GID samples produce similar luminescence after UV LED and white LED exposure, while ART R-GID shows dimmer and shorter-lasting luminescence due to uneven pigment distribution caused by longer curing times. In addition, UV LED illumination produces brighter and more durable luminescence compared to white LED. Longer exposure time results in more persistent afterglow